6-Gingerol delays tumorigenesis in benzo[a]pyrene and dextran sulphate sodium-induced colorectal cancer in mice (2020)
Colorectal cancer (CRC) has been linked to dietary consumption of benzo[a]pyrene (B[a]P). 6-Gingerol (6-G), a component of ginger has been reported to possess anti-inflammatory and antioxidant activities, but little is known regarding the mechanism of 6-G in CRC chemoprevention. We therefore investigated the effect of 6-G on B[a]P. and dextran sulphate sodium (DSS) induced CRC in mice. Mice in Group I and Group II received corn oil and 6-G orally at 2 ml/kg and 100 mg/kg, respectively for 126 days. Group III were administered 125 mg/kg of B [a]P for 5 days followed by 3 cycles of 4% dextran sulphate sodium (DSS). Group IV received 6-G for 7 days followed by co-administration with 125 mg/kg of B[a]P. for 5 days and 3 cycles of 4% DSS. Tumor formation was reduced and expression of Ki-67, WNT3a, DVL-2 and p-catenin following 6-G exposure. Also, 6-G increases expression of APC, P53, TUNEL positive nuclei and subsequently decreased the expression of TNF-a, IL-1p, INOS, COX-2 and cyclin D1. 6-G inhibited angiogenesis by decreasing the concentration of VEGF, Angiopoietin- 1, FGF and GDF-15 in the colon of B[a]P. and DSS exposed mice. Overall, 6-G attenuated B[a]P and DSS-induced CRC in mice via anti-inflammatory, anti-proliferative and apoptotic mechanisms.